How to write an introduction and literature review for your research? - MV Sruthi (Kerala Journal of Ophthalmology)
Writing an engaging Introduction and Literature Review is essential for any research paper. These segments lay the foundation for your research, offering context, pinpointing deficiencies, and substantiating the necessity of your study.